Analysis of salivary factors related to the oral health status in children - Shimomura-Kuroki, Junko; Nashida, Tomoko; Miyagawa, Yukio; Morita, Takao; Hayashi-Sakai, Sachiko (Journal of Oral Science, 2020)
Early detection of oral disease is important to reduce its severity and increase the likelihood of successful treatment. This study aimed to perform a quantitative assessment of the saliva components as a first stage of the research to screen oral homeostasis. Here, saliva secretions collected from children were evaluated, and their constituents were analyzed to investigate the potential correlations between the buffering capacity and a range of salivary factors. Subjects aged 3-16 years in the primary, mixed, or permanent dentition stage, were selected for this study. The following salivary factors were analyzed: flow rate, total protein, total sugar quantifications, and constituent analyses using RT-PCR and western blotting. The associations between each factor and the buffering capacity were then analyzed using multiple regression analysis. Flow rate, BPIFA2 RNA level, histatin 1 and BPIFB1 protein levels as well as female sex were positively associated with buffering capacity. In contrast, total sugar concentration and MUC7 RNA levels showed a negative relationship with the buffering capacity. Some of these constituents may indicate oral homeostasis and are therefore potential biomarkers of oral health status. These results suggest that the analyses of the correlations between oral homeostasis and salivary factors are an effective strategy for identifying the susceptibility to oral diseases.